Individual-and community-level factors associated with anemia among children aged 6-23 months in sub-Saharan Africa: evidence from 32 sub-Saharan African countries - Beminate Lemma Seifu; Getayeneh Antehunegn Tesema (BMC, 2022)
Abstract Background Anemia among children aged 6-23 months is a major public health problem worldwide specifically in sub-Saharan Africa (SSA). Anemia during the childhood period causes significant short-and long-term health consequences. However, there is a paucity of evidence on Anemia among children aged 6-23 months in SSA. Therefore, this study examined the individual- and community-level factors associated with anemia among children aged 6-23 months in sub-Saharan Africa. Methods A secondary data analysis was done based on the most recent Demographic and Health Survey (DHS) of 32 sub-Saharan African countries. A total weighted sample of 51,044 children aged 6-23 months was included for analysis. We have used a multilevel proportional odds model to identify predictors of severity levels of anemia. Variables with p < 0.2 in the bivariable analysis were considered for the multivariable analysis. In the multivariable multilevel proportional odds model, the Adjusted Odds Ratio (AOR) with the 95% Confidence Interval (CI) was reported to declare the statistical significance and strength of the association. Results In this study, about 76.6% (95% CI: 76.2%, 76.9%) of children aged 6-23 months in sub-Saharan Africa were anemic. In the multivariable multilevel proportional odds model, being female, being aged 18-23 months, higher level of maternal education, being larger size at birth, belonging to a wealthier household, getting four ANC visits and above, advanced maternal age, and belonging to a community with high maternal education were significantly associated with lower odds of higher levels of anemia. On the other hand, being twin birth, being smaller size at birth, being of a higher order of birth, having fever in the last two weeks, and distance to a health facility were significantly associated with higher odds of higher levels of anemia. Conclusion The study found that more than three-fourths of children aged 6-23 months in sub-Saharan Africa were anemic. This finding proved that the severity levels of anemia among children in sub-Saharan Africa remain a serious public health concern. Therefore, to curve this problem enhancing maternal education, promoting maternal health service utilization, and improving health care access is crucial. In addition, health care providers better give special emphasis to twin births, higher-order birth, and those belonging to poor households to reduce the incidence of anemia among children aged 6-23 months in SSA.